2016
DOI: 10.1007/s00167-016-4076-3
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted total knee arthroplasty may lead to improvement in quality-of-life measures: a 2-year follow-up of a prospective randomized trial

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
122
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(132 citation statements)
references
References 35 publications
3
122
0
2
Order By: Relevance
“…Six-month manual versus robotic TKA WOMAC scores are still potentially relevant. Liow et al26 performed a randomized controlled trial of 60 knees (31 robotic assisted and 29 manual), and found the robotic-assisted cohort to have higher Short Form (SF)-36 quality of life measures. Specifically, the group noted a significant difference in SF-36 vitality (p ¼ 0.03), emotional role (p ¼ 0.02), and a larger number of patients reaching SF-36 vitality minimum clinically important difference (48 vs. 14%, p ¼ 0.009), all in favor of the robotic group.…”
mentioning
confidence: 99%
“…Six-month manual versus robotic TKA WOMAC scores are still potentially relevant. Liow et al26 performed a randomized controlled trial of 60 knees (31 robotic assisted and 29 manual), and found the robotic-assisted cohort to have higher Short Form (SF)-36 quality of life measures. Specifically, the group noted a significant difference in SF-36 vitality (p ¼ 0.03), emotional role (p ¼ 0.02), and a larger number of patients reaching SF-36 vitality minimum clinically important difference (48 vs. 14%, p ¼ 0.009), all in favor of the robotic group.…”
mentioning
confidence: 99%
“…15 Furthermore, the CT scan-based patient-specific three-dimensional joint rendering has been shown to enhance preoperative planning. 16 These reasons, as well as potentially many others, are likely to contribute to the 1-year outcome results in RAA patients.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Several controlled 9,11,12,29 and noncontrolled 30,31 trials have demonstrated that the use of this robotic system increases the accuracy in restoration of mechanical axis within AE 3 degrees (from neutral alignment) during TKA, 27 without significantly increasing surgical time compared with conventional procedures. 9,11,29 Furthermore, Liow et al 11 showed that patients undergoing robotic-assisted TKA might score better in SF-36 vitality and emotional components at 2 years postoperatively. However, other studies have not seen this difference, 12,29 and a significant improvement in range of motion, function, and quality of life in the mid and long terms with the use of Robodoc has yet to be determined.…”
Section: Robodocmentioning
confidence: 99%
“…Liow et al found one periprosthetic joint infection requiring revision surgery in 31 patients who underwent robotic-assisted TKA and 2 patients with deep vein thrombosis. 11 Siebert et al 49 described wound complications in 3 of 70 patients. Park and Lee 50 in a randomized study of 32 patients allocated to robotic-assisted TKA reported one surgical site infection, one patellar tendon rupture, two periprosthetic fractures, and one neurovascular injury.…”
Section: Surrogate Outcomesmentioning
confidence: 99%
See 1 more Smart Citation